Studies on the early hydration of two modifications of ye'elimite with gypsum - Jansen, Daniel; Spies, Alexandra; Neubauer, Jürgen; Ectors, Dominique; Götz-Neunhoeffer, Friedlinde (Cement and Concrete Research, 2017)
Two modifications of ye'elimite (namely orthorhombic ye'elimite (stoichiometric CA) and iron-containing cubic ye'elimite (CAF)) were synthesized and the reactions without additional sulfate and with gypsum were tracked by means of heat flow calorimetry. Without gypsum the reaction differs significantly for both modifications while the addition of gypsum leads to almost comparable reactions. With addition of gypsum two distinct heat flow maxima could be detected while the reaction without gypsum showed only one distinct maximum for both modifications. For the systems with gypsum additional experiments were performed namely in-situ XRD, NMR, thermodynamic modeling, TGA and pore solution composition. It could be shown that the reaction with gypsum shows two steps of ettringite precipitation for both modifications. The two steps show significant differences. During the first step of ettringite precipitation gypsum and ye'elimite and free water are consumed forming ettringite and a highly hydrated AH. The second ettringite precipitation is powered by ye'elimite consumption but no further gypsum dissolution. In addition, water is removed from the AH used up for the second ettringite precipitation. The two modifications of ye'elimite react comparable with gypsum but show slightly different heats of hydration when reacting with the same calcium sulfate (gypsum) during early hydration; this is due to slightly lower reaction turnover of the cubic, iron-containing modification leading to slightly reduced ettringite formatio